2009
DOI: 10.4049/jimmunol.0803278
|View full text |Cite
|
Sign up to set email alerts
|

The Presumed Hyporesponsive Behavior of Rheumatoid Arthritis T Lymphocytes Can Be Attributed to Spontaneous Ex Vivo Apoptosis rather than Defects in T Cell Receptor Signaling

Abstract: Genetic associations and the clinical success of compounds targeting TCR costimulatory proteins suggest an active role for TCR signaling in the initiation and perpetuation of rheumatoid arthritis (RA). Paradoxically, T cells isolated from affected joints in RA show impaired proliferative and cytokine responses following stimulation with mitogens and recall Ags attributed in part to chronic T cell exposure to oxidative stress and inflammatory cytokines. Therefore, it is uncertain how local autoreactive TCR sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 60 publications
1
13
0
Order By: Relevance
“…The apparently ‘unorthodox’ finding of the hyporesponsive AIA splenocytes compared with normal splenocytes (figure 5A), is in agreement with the literature demonstrating the paradoxical hyporesponsiveness of ex-vivo-stimulated RA T cells, compared with normal T cells 2325…”
Section: Resultssupporting
confidence: 89%
“…The apparently ‘unorthodox’ finding of the hyporesponsive AIA splenocytes compared with normal splenocytes (figure 5A), is in agreement with the literature demonstrating the paradoxical hyporesponsiveness of ex-vivo-stimulated RA T cells, compared with normal T cells 2325…”
Section: Resultssupporting
confidence: 89%
“…A number of studies have suggested that macrophages, T lymphocytes and proliferating synovial cells are very likely to play a major role in the pathogenesis of this disease [49][50][51][52]. The pro-inflammatory cytokines such as IL-1β, IL-6, and TNF-α, produced by the activated T cells and macrophages [53] appear to be involved in the initiation and perpetuation of rheumatoid arthritis.…”
Section: Discussionmentioning
confidence: 96%
“…Various studies have suggested the increased production of pro-inflammatory cytokines by the activated T cells and macrophages [14][15][16][17][18][19][20][21]. These pro-inflammatory cytokines are considered to play a prominent role in the pathogenesis of rheumatoid arthritis, and the regulation of these cytokine levels in arthritic subjects is one of the approaches to the treatment of arthritis [10].…”
Section: Measured Pro-inflammatory Cytokines Concentration Of Cytokinmentioning
confidence: 99%
“…The common pathway for the RA is likely initiated by various humoral signaling agents including activation of pro-inflammatory cytokines, such as interleukin-1b (IL-1b) and tumor necrosis factor-a (TNF-a) [6][7][8][9][10][11], and production of reactive oxygen species (ROS) and reactive nitrogen species (RNS). Studies have suggested that macrophages, T lymphocytes, and proliferating synovial cells very likely play a major role in the pathogenesis of this disease by producing IL-1b, IL-6, and TNF-a [12][13][14][15][16][17][18][19][20]. Likewise, the ROS are products of normal cellular metabolism but their excessive formation is a primary cause, or a downstream consequence, of tissue injury that leads to many pathological conditions such as cancer, cardiovascular disease, atherosclerosis, and RA [21][22][23].…”
Section: Introductionmentioning
confidence: 99%